Endogenous ATP–powered nanomotors directing neural stem cell differentiation for Parkinson’s disease treatment - Miaomiao Ding; Bin Chen; Jing Xiao; Jinghui Rong; Ye Feng; Chao Gao; Dailing Du; Yingfeng Tu; Fei Peng (Proceedings of the National Academy of Sciences, 2026)
Transplantation-free neuron regeneration remains attractive yet unsolved for reversing Parkinson’s disease (PD). Here, we present enzyme-driven mesoporous gold nanomotors (Apyrase@Au) that leverage endogenous biochemical energy for spatiotemporally controlled promotion of neural stem cell (NSC) differentiation, without exogenous stem cell transplantation. By catalyzing endogenous adenosine triphosphate (ATP) hydrolysis, Apyrase@Au nanomotors simultaneously generate directional propulsion and localized signaling messenger protons. These protons induce calcium influx and activate quiescent NSCs within the ventricular-subventricular zone of PD mice, directing their differentiation into functional neurons and alleviating moving dysfunction. The bioenergy-converting system imparts dual functionality to active matter, propelling while concurrently yielding bioactive products. This work demonstrates the potential of ATP-powered nanomachines as a self-sustaining and targeted biointerface, offering a promising strategy for promoting NSC differentiation and alleviating moving dysfunction in degenerative diseases.